International criminal procedure - Boas, Gideon (Cambridge : Cambridge University Press, 2011)
'Volume 3 of the International Criminal Law Practitioner Library completes the review of international criminal law begun in Volumes 1 and 2, which analyse the forms of responsibility and the elements of the core crimes. This volume reviews the procedural law and practices of the international criminal tribunals from investigation to trial, appeal, and punishment, and examines the framework within which the substantive law operates. The authors present a critical study of those procedures that are essential to effective investigations and fair trials, and explore how the ICC, ICTY, and ICTR - as well as the SCSL and other internationalised tribunals, where relevant - have shaped the evolution of international criminal procedure in order to meet new challenges and changing circumstances. The key jurisprudence and rule amendments up to 1 December 2009 have been surveyed, making this a highly relevant and timely work'--
Includes bibliographical references and index.
Keywords: International criminal courts -- Rules and practice; Criminal procedure (International law); Criminal justice, Administration of; Complementarity (International law)